Communication Patterns and Student Ethics Towards Lecturers in Using Whatsapp Applications - Doho, Yohannes Don Bosco; Safrul, Safrul; Ghazali, Al; Surur, Miftahus (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to describe the pattern of communication and good ethics between students and lecturers in communicating via Whatsapp in accordance with morals and courtesy. The research method used is qualitative research with a descriptive approach . The process of collecting data is done by means of literature study. This method is a literature review from various sources and relevant references. From the results of the literature study above, ethics in communicating in contacting lecturers is very important to avoid misunderstandings between students and lecturers. Students must also pay attention to the format of the message to be conveyed to the lecturer. The ethics that are considered in communicating via WhatsApp with lecturers are pay attention to the right time to contact the lecturer, start the message with greetings, introduce yourself, make sure the choice of words or punctuation is good, end the message with thanks and greetings.